Pengaruh Model Boarding School Terhadap Kecerdasan Spiritual Siswa : (Studi Kasus Di SMPIT Al-Ghazali) - Izza Farohna Bella; Badrut Tamami (Program Studi Pendidikan Agama Islam, 2022)
The development of educational models in the modern era is currently popular with the concept of boarding school based. The main orientation of this concept is the intelligence of students both cognitively, intellectually, emotionally and especially spiritually. The purpose of this study was to determine the effect of the boarding school model on students’ spiritual intelligence. The basis of this research with a quantitative approach. Simple regression analysis model in collecting data thtough questionnaires based on the linkert scale, the number of respondets or students is 76 students. The results of the study by passing 4 standardized test ranging from validity to normality. Showed that the boarding school model had a significant effect with an r value of 0.331 or 33.1%. Based on the research data, it can be concluded that the effect of the boarding school model on students’ spiritual intelligence is 33.1% or in the low category, which means the rest is influenced by other factors